(untitled) (Bangladesh Journal of Medical Education, 2024)
Emotional Intelligence (EI) combines the important aspects of interpersonal and intrapersonal relationship, adaptability, mood and stress management skills which has an effect on students academic performance. It is also widely accepted as one of the dominant factor contributing to superior and professional performance. This cross-sectional study was aimed to measure the score of different dimensions of emotional intelligence of undergraduate medical students of Bangladesh to categorize the undergraduate medical students by their academic performance and sociodemographic background. The objectives of the study were also to relate the level of different dimensions of emotional intelligence with their academic and sociodemographic background using Genos Emotional Inventory (concise version) and additional questions relevant to the performance of the students. Genos Emotional Intelligence Inventory questionnaire (concise version) consists of 31 items with 5 answering options for each as per Likert scale and 5 additional questions related to academic performance. Confidentiality of the data and participants were maintained all through. Data were analyzed using SPSS 19. To determine internal consistency of the questionnaire Cranach’s alpha was used. This Study was conducted at selected medical colleges of Bangladesh .out of nine, five were government and four were non- government, five from Dhaka and four from outside of Dhaka. Study period was one year. Undergraduate students of all four phase of MBBS course were study population. Sample size was 904, pretested self-administered semi-structured questionnaire were used to collect data. Medical college and students were selected by adopting convenient sampling technique. This study revealed that, mean score in male was 64.47± 8 and female it was 67.2 ± 38.14. The result of current study indicate that female undergraduate students had higher EI than their male counterpart. Among the different sub-groups of EI highest score EAO sub- group ,mean score was in male 70.90 ±13.48 and in female 72.47 ±12.34 . This study also showed the correlation of two variables (EI and Academic Performance) based from Pearson Correlation Coefficient is significant. It means that when EI of undergraduate medical students increases, their academic performance also trends to increase. Here nearly 9.9% of the variance in academic performance is explained by independent variables together. This study recommended that EI should be incorporated in undergraduate medical curriculum and should be taught with the details of learning outcome what are desired from registered medical graduate so that learning can be turned into practice. BJME, Volume-15, Issue-01, January 2024: 57-66